2018
DOI: 10.1253/circj.cj-17-0392
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Gaps in the Management of Probable Familial Hypercholesterolemia and Cardiovascular Disease

Abstract: in order to identify insured patients with a high probability of FH. The study protocol has been reported in detail. 4 In short, inclusion in the study required peak LDL-C documented in the computerized database that was above age-dependent cut-offs associated with a high probability of FH in the general population, based on the modified MEDPED (make early diagnosis prevent early death) criteria: LDL-C >190 mg/dL in individuals <20 years of age, LDL-C >220 mg/dL at 20-29 years, and LDL-C >250 mg/dL at ≥30 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
(18 reference statements)
3
13
0
Order By: Relevance
“…This is consistent with a previous report on 1690 individuals with clinical diagnosis of FH in which those with previous CVD events had higher classical CVD risk factors with the exception of smoking. 33 When we stratified the FH cohorts based on type of mutation (nonsense vs missense mutation), we found that individuals with nonsense mutation had an overall more severe phenotype (namely, higher total cholesterol, and LDL-C) in FH Gothenburg with similar trend in FH Milano. This is consistent with the possible presence of residual LDLR activity in missense mutations, which may mitigate the FH phenotype.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is consistent with a previous report on 1690 individuals with clinical diagnosis of FH in which those with previous CVD events had higher classical CVD risk factors with the exception of smoking. 33 When we stratified the FH cohorts based on type of mutation (nonsense vs missense mutation), we found that individuals with nonsense mutation had an overall more severe phenotype (namely, higher total cholesterol, and LDL-C) in FH Gothenburg with similar trend in FH Milano. This is consistent with the possible presence of residual LDLR activity in missense mutations, which may mitigate the FH phenotype.…”
Section: Discussionmentioning
confidence: 86%
“…* .244 Xanthelasmas, n (%) 9 (7) 5 (13) .33 Arcus cornealis, n (%) † 27 (22) 17 (44) .008 Active smoking, n (%) 20 (16) 4 (10) .001 Hypertension, n (%) 20 (16) 13 (33) .019 Diabetes, n (%) 3 (2) 4 (10) . (28) .033…”
Section: Supplementary Datamentioning
confidence: 99%
“…2019; 29 unaware that they carry genetic mutations. These rates are even lower among medically underserved populations [8][9][10][11] that historically have inadequate access to, or reduced utilization of, highquality health care. 12 These populations include racial/ethnic minority populations, socioeconomically disadvantaged populations, underserved rural populations, and sexual and gender minorities.…”
Section: Leveraging Implementation Science To Address Health Disparitmentioning
confidence: 99%
“…12 These populations include racial/ethnic minority populations, socioeconomically disadvantaged populations, underserved rural populations, and sexual and gender minorities. 12 Disparities in uptake of evidencebased guidelines for HBOC 10 , LS 9 and FH 8,11 have been documented and demonstrate a critical challenge in the implementation of genomic medicine.…”
Section: Leveraging Implementation Science To Address Health Disparitmentioning
confidence: 99%
See 1 more Smart Citation